(untitled) (Contemporary Mathematics, 2025)
Idempotents play a basic role in the study of algebras. Peirce decomposition induced by an idempotent is an important tool in the structure theory of non-associative algebras. In this note, we investigate the Peirce decomposition of a unital quasi Jordan algebra.